Effect of a combined mulberry-sage dietary supplement on food craving and body weight: a pilot clinical trial: Mulberry and Sage extract for food craving - Cicero, Arrigo F.G.; Fogacci, Federica; Veronesi, Maddalena; Di Micoli, Antonio; Bove, Marilisa (Progress in Nutrition, 2023)
Background and aim: Overweight and obesity are largely prevalent in developed and developing countries, being risk factors for type 2 diabetes, cardiovascular disease and all-causes mortality. The aim of this pilot study was to test the effect of a combined mulberry-sage dietary supplement on food craving and body weight in healthy overweight subjects. Methods: This is a randomized, single-blind, clinical trial, involving 40 overweight healthy subjects randomized to assume a combined dietary supplement containing mulberry and sage extracts vs. standard diet. The volunteers were visited after 14, 28 and 56 days, sampling anthropometric data and the scores of the Food Cravings Questionnaire–Trait (FCQ–T) and the Short Form Health Survey 36 (SF-36). Results: The active treatment waswell-tolerated and all patients completed the study. After 56 days of intake, the subjects treated with the tested dietary supplement on top of a standard diet experienced a significant improvement in FCQ-T, SF-36 and percentage fat mass versus standard diet only treated ones (p<0.05). FCQ-T improved just after 14 days versus placebo in the dietary supplement treated subjects, only. Conclusions: In conclusion, the tested dietary supplement seemed to mildly but significantly support body weight loss by decreasing food craving in healthy overweight subjects.